Flowmouse: A computer vision-based pointing and gesture input device - Wilson, Andy; Cutrell, Ed (INTERACT'05 Proceedings of the 2005 IFIP TC13 international conference on Human-Computer Interaction, 2005)
We introduce FlowMouse, a computer vision-based pointing device and gesture input system. FlowMouse relies on optical flow techniques and a capacitive touch sensor to enable and disable interaction. By using optical flow rather than a more traditional tracking based method, FlowMouse is exceptionally robust, simple in design, and offers opportunities for fluid gesture-based interaction that go beyond merely emulating pointing devices such as the mouse. We present a Fitts law study examining pointing performance, and discuss applications of the optical flow field for gesture input.